2021
DOI: 10.1038/s41467-021-25432-7
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of longitudinal metastatic tumors reveals genomic alterations and immune landscape dynamics associated with pembrolizumab sensitivity

Abstract: Serial circulating tumor DNA (ctDNA) monitoring is emerging as a non-invasive strategy to predict and monitor immune checkpoint blockade (ICB) therapeutic efficacy across cancer types. Yet, limited data exist to show the relationship between ctDNA dynamics and tumor genome and immune microenvironment in patients receiving ICB. Here, we present an in-depth analysis of clinical, whole-exome, transcriptome, and ctDNA profiles of 73 patients with advanced solid tumors, across 30 cancer types, from a phase II baske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 91 publications
1
45
0
Order By: Relevance
“…The tumour microenvironment can also provide important clues as to how an individual tumour and patient may respond to immunotherapy. Recently, this has included the T-cell receptor (TCR) repertoire of tumour-infiltrating lymphocytes [ 81 83 ]. TCR repertoire diversity in peripheral blood prior to treatment initiation could also represent a predictive biomarker to guide the use of immunotherapy [ 84 , 85 ].…”
Section: Opportunities: Emerging Landscape and Future Clinical Applic...mentioning
confidence: 99%
“…The tumour microenvironment can also provide important clues as to how an individual tumour and patient may respond to immunotherapy. Recently, this has included the T-cell receptor (TCR) repertoire of tumour-infiltrating lymphocytes [ 81 83 ]. TCR repertoire diversity in peripheral blood prior to treatment initiation could also represent a predictive biomarker to guide the use of immunotherapy [ 84 , 85 ].…”
Section: Opportunities: Emerging Landscape and Future Clinical Applic...mentioning
confidence: 99%
“…Evaluation of other available tissue biomarkers, such as sodium iodine transporter, requires adequate samples that can only be obtained in an invasive manner, and is hindered by spatial and temporal heterogeneity. These data underline the challenge to identify a reliable biomarker among the systemic immune components with a clear predictive value for DTC patients, since the development and maintenance of an immune microenvironment has shown clear associations with individual outcome ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used CIBERSORTx cell sorting technology to analyze the RNA sequencing data to compare the cellular composition of the tissues of complete responders to that of poor responders. In another study, CIBERSORTx showed that a subset of patients with advanced solid cancers, characterized by early-on increase of T follicular helper cells after treatment with pembrolizumab immunotherapy, had a favorable progression-free survival [ 27 ]. The main differences that we found were more activated CD4 memory T-cells and neutrophils in responders.…”
Section: Discussionmentioning
confidence: 99%